Repression of Rgg but not upregulation of LacD.1 in emm1-type covS mutant mediates the SpeB repression in group A Streptococcus - Chuan Chiang-Ni; Teng-Ping Chu; Jiunn-Jong Wu; Cheng-Hsun Chiu (Frontiers in Microbiology, 2016)
CovR/CovS is an important two-component regulatory system in human pathogen group A Streptococcus (GAS). Epidemiological studies have shown that inactivation of the sensor kinase CovS is correlated with invasive clinical manifestations. The phosphorylation level of response regulator CovR decreases dramatically in the absence of CovS, resulting in the derepression of virulence factor expression and an increase in bacterial invasiveness. Streptococcal pyrogenic exotoxin B (SpeB) is a cysteine protease and is negatively regulated by CovR; however, the expression of SpeB is almost completely repressed in the covS mutant. The present study found that in the emm1-type A20 strain, nonphosphorylated CovR acts as a transcriptional repressor for SpeB-positive regulator Rgg. In addition, the expression of Rgg-negative regulator LacD.1 is upregulated in the covS mutant. These results suggest that inactivation of Rgg in the covS mutant would directly mediate speB repression. The current study showed that overexpression of rgg but not inactivation of lacD.1 in the covS mutant partially restores speB expression, indicating that only rgg repression, but not lacD.1 upregulation, contributes to the speB repression in the covS mutant.